The Influence of Eating Culture, Physical Activity, Smoking Habits and Gender on the Incidence of Hypertension to Pre late Adulthood in Padangsidimpuan General Hospital - Afriani, Miskah; Wahyuni, Wahyuni; Harahap, Milna Chairunnisa (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Hypertension is a condition with blood pressure exceeding normal limits. If hypertension is not well controlled it can lead to damage to blood vessels and can even lead to the risk of death. According to Indonesia's health profile in 2013, there is an increasing prevalence of hypertension to 9.55%. Data obtained from Padangsidimpuan General Hospital, the number of hypertension patients increased from 2014-2016. Hypertension ranks 4th out of 10 major diseases in Padangsidimpuan General Hospital. This study aims to analyze the influence of eating culture, physical activity, smoking habits and gender on the occurrence of hypertension atPadangsidimpuan General Hospital. The type of research used is analytic study with cross-sectional design. The population in this study were all pre-hypertension suffering as many as 55 people. The sample is the entire population number used as the sample that is as much as 55 people. Data were obtained from Padangsidimpuan General Hospital and through interview result using questionnaire. The method analysis used was univariate, bivariate, and multivariate by using multiple regression logistic methods. The results showed statistical test results of independent variables eating culture shows there is a significant influence of independent variables with the dependent variable (0,003 < 0,05). Physical activity obtained Sig- value (0,048) means there are a significant influence independent variables with dependent. Smoking habits obtained (0,043) means there are a significant influence independent variables with dependent. Gender variable shows there is no significant influence of the independent variable with dependent. The most influential variable is eating culture. It is suggested to respondents to improve their healthy lifestyle to reduce the incidence of hypertension by reducing eating fatty foods, get exercise routine and stop smoking